Implementasi Kebijakan Pariwisata Bahari Di Kota Di Kota Semarang : (Studi Kasus Di Kampung Tambak Lorok Kelurahan Tanjung Mas) - Sri Suwitri; Tri Yuniningsih; Rezky Ghoffar Ismail (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2019)
Fisherman Village Development in Tambak Lorok is one of the maritime tourism destinations which is the step of the Semarang City Government to improve the welfare of the people in Tambak Lorok Village. This study aims to examine the implementation of tourism policies in the village of Tambak Lorok, Tanjung Mas Village, Semarang City. The method used: qualitative descriptive research methods, gathering information using observation and interview techniques, determining informants using snowball sampling technique. The results of the study: (a) The government has facilitated the establishment of marine tourism villages in Tambak Lorok (b) patterns of community behavior are difficult to change so that it can hinder development and (3) cooperation between actors in the development of maritime tourism is not optimal. The recommendations that an be given are: the need for an increase in joint commitment and subsequent researchers are advised to take a different focus from this research.